Catalytic Pyrolysis of High-density Polyethylene (HDPE) by using Multiple Stage Reactor - Mohd Supian, Muhammad Shaukie (Progress in Engineering Application and Technology, 2022)
Plastics have rapidly gained favor with the general public due to their high durability, low production cost, and lightweight nature. But it has a major problem during disposal treatment which leads to negative impacts on health and the environment. This pyrolysis process converts the plastic into energy (liquid black oil) and value-added products (char). There is a growing interest in the pyrolysis of waste plastics, where the plastic is thermally degraded at moderate temperature ( 450°C) in the absence of oxygen to produce shorter molecular chains and low molecular weight molecules. This project is conducted to investigate the correlation of multiple stage reactors with the effect of temperature on the yield and quality of produced liquid oil. Thus, to synthesize and characterize the yield, I would be using Fourier Transform Infrared Spectroscopy (FTIR), latent heat, density, and viscosity. The expected outcome is to investigate the correlation between temperature to achieve an optimum temperature in the parameter that has been listed with three different ranges of temperature and different times. This project used a multistage reactor and nickel catalyst on the reaction for this project and the method may be a shift methodology with multiple heating steps to realize bound technical advantages. shift is mostly thought of to be endothermal though it includes exoergic and endothermic reactions. With only nine samples of yield, the output yields then go through the analysis with latent heat of blank catalyst with 150°C was 30.334 kJ/kg of the mass. Density also got 0.9512 g/cm3 when measuring the mass of the sample with a pycnometer. The viscosity then in medium structure yields on 150°C of the temperature. FTIR analysis shows the aliphatic compound on the graph was total in 2924.45 cm-1, 68.37 %T. The retention time of 150°C yields 9 gram of oil mass when it reaches 5 minutes of time taken. The maximum point of time taken is when it reaches 50 gram of yield in 30 minutes during the pyrolysis process.